2009
DOI: 10.1021/np900336f
|View full text |Cite
|
Sign up to set email alerts
|

Carteriosulfonic Acids A−C, GSK-3β Inhibitors from a Carteriospongia sp.

Abstract: Modulators of Wnt signaling have therapeutic potential in a number of human diseases. A fractionated library from marine invertebrates was screened in a luciferase assay designed to identify modulators of Wnt signaling. A fraction from a Carteriospongia sp. sponge activated Wnt signaling and was subsequently shown to inhibit GSK-3β, which inhibits Wnt signaling through phosphorylation of β-catenin. Three novel natural products, carteriosulfonic acids A (1), B (2) and C (3), were identified as active constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…sponge collected in the Philippines, also inhibited GSK-3β, potentially through an allosteric mechanism. 290 These results suggest that optimization of marine-derived compounds as exemplified above could realize highly selective negative allosteric modulators of GSK-3β, particularly as compared to inhibitors competing with the highly conserved ATP binding site.…”
Section: Enzyme Modulatorsmentioning
confidence: 92%
“…sponge collected in the Philippines, also inhibited GSK-3β, potentially through an allosteric mechanism. 290 These results suggest that optimization of marine-derived compounds as exemplified above could realize highly selective negative allosteric modulators of GSK-3β, particularly as compared to inhibitors competing with the highly conserved ATP binding site.…”
Section: Enzyme Modulatorsmentioning
confidence: 92%
“…Using the RIVA method, we tested a subfraction of the MICL, a marine natural product library and a unique resource for the discovery of novel small molecules with biological activities in a variety of systems [63,64]. Screens by means of MICL have already identified novel modulators of diverse biological processes, such as Breast Cancer gene 2 (BRCA2)-deficient chemotherapy resistance, protein kinase C ζ (PKCζ), hypoxia-inducible factor 1 (HIF-1), wingless-related integration site (Wnt) signaling, phenotype induction in zebrafish and cystathionine β-synthase activity [63,[98][99][100][101][102][103]. Alkaloids from marine sponges have been demonstrated to stimulate initial development stages of agricultural plants [104].…”
Section: Methods Application By Semi-purified Fractions Of Marine Invementioning
confidence: 99%
“…Compounds 120 – 127 [ 43 ] and phylloamide A ( 128 ) [ 44 ] were also isolated from the South China Sea sponge. Carteriosulfonic acids A–C ( 129 – 131 ) [ 45 ] and 132 [ 46 ] were respectively isolated from two specimens collected at Philippines and Fiji. Bioassay results suggested that 128 – 130 had an inhibitory effect on the growth of glycogen synthase kinase-3β (GSK-3β), with IC 50 values of 12.5, 6.8, and 6.8 μM, respectively.…”
Section: Natural Products From Phyllospongia Spmentioning
confidence: 99%